Dolutegravir 50 mg thrice weekly plus atazanavir 400 mg daily in a long-term virologically suppressed HIV-infected patient. (June 2017) - Lanzafame, Massimiliano; Lattuada, Emanuela; Nicolè, Stefano; Rigo, Fabio; Cucchetto, Giulia; Concia, Ercole; Vento, Sandro
Highly active antiretroviral therapy (HAART) has changed the natural course of HIV infection. However, the toxicities associated with long-term use of nucleoside reverse transcriptase inhibitors (NRTIs) have led to the assessment of dual-therapy approaches with less toxicity. Atazanavir and dolutegravir have antiviral potency, tolerability and favourable metabolic profile. In suppressed HIV-infected patients, with NRTIs-related toxicity effects, the association of atazanavir and dolutegravir, favoured by their positive pharmacokinetics interaction, could be used as 'maintenance' antiretroviral therapy. We report a case report about one HIV-infected patient, on HAART and with a persistent suppression of HIV RNA, switched to dolutegravir 50 mg three times weekly plus atazanavir 400 mg once daily, as 'maintenance antiretroviral therapy', with persistence of viral suppression.